2014
DOI: 10.1371/journal.pone.0108748
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stressor Exposure Modifies Plasma Exosome-Associated Heat Shock Protein 72 (Hsp72) and microRNA (miR-142-5p and miR-203)

Abstract: Exosomes, biologically active nanoparticles (40–100 nm) released by hematopoietic and non-hematopoietic cells, contain a variety of proteins and small, non-coding RNA known as microRNA (miRNA). Exposure to various pathogens and disease states modifies the composition and function of exosomes, but there are no studies examining in vivo exosomal changes evoked by the acute stress response. The present study reveals that exposing male Fisher 344 rats to an acute stressor modulates the protein and miRNA profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 44 publications
2
51
0
1
Order By: Relevance
“…The Plant EV Proteome Changes Little in Response to P. syringae Infection Mammalian cells modify the composition and function of exosomes during stress (Clayton et al, 2005;Beninson et al, 2014). We questioned whether plant cells also might modify the protein content of EVs during bacterial infection.…”
Section: Comparisons With Other Proteomesmentioning
confidence: 99%
“…The Plant EV Proteome Changes Little in Response to P. syringae Infection Mammalian cells modify the composition and function of exosomes during stress (Clayton et al, 2005;Beninson et al, 2014). We questioned whether plant cells also might modify the protein content of EVs during bacterial infection.…”
Section: Comparisons With Other Proteomesmentioning
confidence: 99%
“…EVs derived from pathogen-infected mammalian cells have a variety of proinflammatory functions that increase the efficacy of innate immunity. It has been recently reported that acute stressor exposure, such as to heat and oxidative stress, also modifies EV miRNAs associated with the TLR-mediated inflammatory response [36][37][38]. Importantly, these variations of EV components result from targeted selection, not random incorporation into the MVB [32,39].…”
Section: Reviewmentioning
confidence: 99%
“…TR4 may mediate some components of stress-induced inflammation since restraint stress increased TLR4 expression in rodent brain and blocking TLR4 activity attenuated stress-induced NF-κB activation and the ensuing up-regulation of IL-1β and IL-6 in the prefrontal cortex (Gárate et al, 2011; Gárate et al, 2013; Gárate et al, 2014). Several DAMPs have been shown to be increased after psychological stressors in a variety of tissues, suggesting that increased DAMPs induced by stress may activate the inflammatory response (Campisi et al, 2003; Fleshner et al, 2004; Campisi et al, 2012; Maslanik et al, 2013; Beninson et al, 2014; Weber et al, 2015). Particular interesting are the findings that acute inescapable tail shock stress increased HMGB1 levels in rodent hippocampus, and central administration of an HMGB1 antagonist diminished the potentiation by stress of LPS-induced increases of IL-1β by hippocampal microglia, suggesting that HMGB1 mediates the priming effect of stress on LPS-stimulated microglia (Weber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%